(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
The article provides a General scheme and principle of operation of a chain transmission with elastic elements. The article presents an analysis of the elements and reasons for reducing the service life of chain gears used in drives of various technological machines. The analysis of existing methods for calculating the service life of the drive roller chain is given. There given an improved method for calculating the service life of the transmission, taking into account the elastic elements of the chain. Also, formula for calculating the service life of a chain transmission with a composite roller, including a rubber sleeve of the transmission chain, is presented.